Penerapan Media Pembelajaran Schoology untuk Meningkatkan Hasil Belajar Mahasiswa - Addin Zuhrotul Aini (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: The purpose of this research is to describe the improvement of learning outcomes of students through the application of Schoology learning. This research method was Classroom Action Research (CAR). The data collection technique used observation and test methods. The results of this study were the learning outcomes in the cycle I showed that students who completed learning were 42% with the highest score of 88. Student learning outcomes in cycle II indicated that students who had complete as much as 93% with the highest score of 90. The average value in the first cycle was 73.39 while the average value for the second cycle was 85.14. The increase in the percentage of completeness from cycle I and cycle II was 51%. From the results of learning cycle II, it can be seen that the indicators of learning success have been achieved. The conclusion of this research is that the learning outcomes of student character education during the learning process using Schoology learning media in the students of the Mathematics Education Study Program of STKIP PGRI Nganjuk have increased. This is indicated by the number of students who completed the first cycle by 42%, increasing to 93% in the second cycle.